Invasive follicular thyroid carcinoma infiltrating trachea - Filipović Aleksandar; Vučković Ljiljana; Mijović Milan (Vojnosanitetski Pregled)
Introduction. Although follicular thyroid carcinoma is a rare malignant tumor, up to 20% of the patients are threatened by potential complications resulting from infiltrating tumor growth into surrounding tissues. Case report. A 66- year-old female came to hospital with the presence of a growing thyroid nodule of the left lobe. Ultrasonic examination showed a 8 cm hypoechoic nodule in the left lobe. Thyroid scintigraphy showed a cold nodule. CT scan and tracheoscopy showed tracheal infiltration without tracheal obstruction. An extended total thyroidectomy was done, with the left jugular vein, strap muscles and tracheal 2 cm long circular resection. The pathologist confirmed invasive follicular thyroid cancer. After the surgery the patient was treated with radioiodine therapy and permanent TSH suppressive therapy. The patient was followed with measurements of the thyroid hormone and serum thyroglobulin level every six months, as well as the further tests (chest xray, ultrasound of the neck and a whole body scintigraphy) were done. After more than three years the patient had no evidence of the recurrent disease. Conclusion. Radical resection of the tracheal infiltrating thyroid cancer with circular tracheal resection and terminoterminal anastomosis followed by radioiodine therapy should be considered the treatment of choice.